Escape from New Babylon - Jenkins, Jerry B.; Fabry, Chris, 1961-; LaHaye, Tim F. (Wheaton, Ill. : Tyndale Kids, 2002)
Judd and Nada must help a stranger escape from New Babylon, and the Young Trib Force wonders if it can trust their new member Chris Traickin.
"Discovering new believers"--Cover.
4.5
5-8
Keywords: Christian fiction; Eschatology -- Fiction; Fantasy; Teenagers -- Fiction; Christian fiction; Eschatology -- Fiction; Teenagers -- Fiction; Fantastic fiction